Intrathecal drug delivery systems for the management of chronic non-cancer pain: protocol for a systematic review of economic evaluations. Issue 7 (15th July 2016) - Duarte, Rui V; Lambe, Tosin; Raphael, Jon H; Eldabe, Sam; Andronis, Lazaros
Abstract : Introduction: Intrathecal drug delivery (ITDD) systems are an option for the management of patients with chronic non-cancer pain, cancer pain and spasticity. Concerns over their invasiveness and high initial costs have led National Health Service (NHS) England to decommission ITDD for patients with chronic non-cancer pain. However, the extent to which this decision is in line with existing economic evidence is unclear. To address this question, we will carry out a systematic review to identify and evaluate the existing evidence on the cost-effectiveness of ITDD for chronic non-cancer pain. Methods and analysis: A high-sensitivity search strategy will be employed in Cochrane Library, MEDLINE, EMBASE, Web of Science, NHS EED, DARE and HTA. Database searches will be complemented by additional searching techniques. Screening of the results will be performed by 2 reviewers independently using predetermined inclusion and exclusion criteria. Full and partial economic evaluations will be included. Data extraction will be carried out using a form created for the purposes of this review. Quality assessment of all included studies will be performed using recommended checklists. Ethics and dissemination: Ethical approval is not required as primary data will not be collected. Findings will be disseminated through peer-reviewed publications and conference presentations. PROSPERO registration number: CRD42016035266.